2018
DOI: 10.2146/ajhp160830
|View full text |Cite
|
Sign up to set email alerts
|

Improving medication-related clinical decision support

Abstract: Standardization, integration of patient-specific parameters, and consideration of human factors design principles are central to realizing the potential benefits of medication-related CDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 65 publications
1
76
0
2
Order By: Relevance
“…They suggested that sensitivity and specificity of alerts should always be considered, with an emphasis on high specificity to decrease alert fatigue. They also proposed tiering of alerts to improve acceptance and consideration of human factors in CDS design [20] The analytic reviews analyzed the features of previously implemented CDS tools. Several reviews examined alert use, generally finding acceptance rates to be low [21] and override rates to be high [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that sensitivity and specificity of alerts should always be considered, with an emphasis on high specificity to decrease alert fatigue. They also proposed tiering of alerts to improve acceptance and consideration of human factors in CDS design [20] The analytic reviews analyzed the features of previously implemented CDS tools. Several reviews examined alert use, generally finding acceptance rates to be low [21] and override rates to be high [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Using the techniques of improving relevance, soliciting feedback, customization, measurement of outcomes and metrics, and iteration, the effects of CDS on burnout can be ameliorated. [20,24,97] -Role tailoring of alerts [21,82] -Tiering of alerts [20,80] -Iterative design [25] Harmful -Interruptive or hard stop alerts [21,25,80] -Lack of "right information" [18] -Lack of relevance [80,97,108] -Lack of integration [78]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This improvement should include more patient-specific information in order to reduce alert fatigue. 21,22 Second, alerts run in real time, and the system continuously performs searches for new orders and laboratory test values. This feature differs from many commercially available CDSS, in which real-time analysis is not available.…”
Section: Discussionmentioning
confidence: 99%
“…1 EHRs routinely support patient safety by checking for drug allergies, drug-drug interactions, appropriate drug dosages, and duplicate orders. 2 Oftentimes, this support comes in the form of interruptive alerts that help prevent a user from doing the wrong thing. However, there is another approach.…”
Section: Background and Significancementioning
confidence: 99%